Characteristics of body tissue composition and functional traits in junior football players - Burdukiewicz, A.; Chmura, J.; Pietraszewska, J.; Andrzejewska, J.; Stachon, A.; Nosal, J. (Human Movement, 2013)
Purpose: The aim of this study was to examine the body tissue composition and functional traits of young football players. Methods: Analysis was performed on 23 junior football players. Body mass and height were measured. Bioelectrical impedance was used to assess the players` body composition (fat mass, muscle mass, body cell mass and extracellular mass). The body mass index, body cell mass index and the extracellular mass/body cell mass ratio were also calculated. Functional traits were assessed by a one-on-one football game in an enclosed space with the objective to score the highest number of goals in a timed setting. Measurements of HR rest, HR max and heart rate reserve were used to evaluate the efficiency of the subjects` cardiovascular systems. Results: Insignificant differences in body tissue composition and cardiovascular efficiency were found regardless of what position was played. Overall, forwards were characterised by having the greatest height, the highest level of active body tissue development and the most efficient cardiovascular systems. Defenders were characterised by having larger body build, while midfielders displayed a significantly greater percentage of extracellular mass and EMC in relation to BCM. Conclusions: The results reveal that trends exist in the body tissue composition and cardiovascular efficiency of football players depending on which position they play. These differences reflect the varied physical efforts players perform during a match and should be taken into consideration when designing training programmes.